2020
DOI: 10.1093/qjmed/hcaa059.009
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes Of Autologous Platelet Gel In Bone Reconstruction Of Defects In Patient With Benign Bony Cystic Lesions

Abstract: Background Although autologous bone grafting is still considered the ‘‘gold standard’’ in bony defect repair, the past century has seen significant advances in the development of valid alternatives to natural bone. Aim of the Work The purpose of the present study is to assess short term clinical and radiographic outcome of bone defect reconstruction by platelet gel mixed with hydroxy appetite/beta tri-calcium phosphate ( HA/B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study presented by Mostafa et al [ 62 ], the authors showed a positive treatment effect of using autologous platelet gel mixed with hydroxy appetite/beta tri-calcium phosphate bone substitutes on reconstructing bone defects after extended curettage surgery for 20 patients with benign bony cystic lesions. The mean follow-up time was 18 months.…”
Section: Research On Using Platelet Gel To Reconstruct Bone Defects I...mentioning
confidence: 99%
“…In a study presented by Mostafa et al [ 62 ], the authors showed a positive treatment effect of using autologous platelet gel mixed with hydroxy appetite/beta tri-calcium phosphate bone substitutes on reconstructing bone defects after extended curettage surgery for 20 patients with benign bony cystic lesions. The mean follow-up time was 18 months.…”
Section: Research On Using Platelet Gel To Reconstruct Bone Defects I...mentioning
confidence: 99%